Epidemiology of Village Chicken Diseases and Associated Risk Factors in Mizoram, India - Deka, Devajani; Bayan, Hitesh; Rajkhowa, T. K . (International Journal of Livestock Research, 2020)
The study was conducted in three districts of Mizoram (India) to investigate the diseases of village chicken and associated risk factors. Constraints of village chicken production were studied in 126 randomly selected households and incidence of diseases was studied on 60 purposively selected farmers having large chicken flock. The diseases and predation were perceived as the major causes of village chicken loss. The seasonal occurrence of diseases was high with heavy mortality in chicks during monsoon and summer which hindered the consistent rearing of large sized chicken flock. Highest mortality was due to New Castle disease followed by other infectious diseases. Ethno veterinary medicine was commonly practiced and the farmers used local herbs namely capsicum/ chilli (hmarcha), turmeric (tengtere), amla (sunhlu) and lemon juice (hatkora) during the disease outbreak and as prophylaxis. Appropriate management along with programmed vaccination against common viral diseases should be practiced to control the loss of village chicken.